PERCEPATAN KEMAMPUAN BERAKAR DAN PERKEMBANGAN AKAR STEK PUCUK Shorea platyclados MELALUI APLIKASI ZAT PENGATUR TUMBUH IBA - Suryo Hardiwinoto; Rixa Riyanti; Widiyatno Widiyatno; Adriana Adriana; Widaryanti Wahyu Winarni; Handojo Hadi Nurjanto; Eko Priyo (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2016)
Shorea platyclados is one of fast-growing Dipterocarp species for enrichment planting in Logged-Over Area (LOA) of tropical rain forests. One of the constrain to supply the seedling for support enrichment planting is the irregular flowering of S. platyclados. Moreover, the vegetative propagation is an alternative method to provide the sustainable seedling for enrichment planting in the LOA. This experiment was carried out to assess the effects of IBA concentrations on rooting ability, the primary and secondary root lengths, and the accumulated number of primary and secondary roots on shoot cutting of S. platyclados. The research was conducted in Completly Randomized Design (CRD) with 5 replications. The treatment was five concentrations of IBA, i.e. 0 ppm, 25 ppm, 50 ppm, 75 ppm, and 100 ppm. The data were analyzed using one-way analysis of variance (one way ANOVA) to determine the effect of IBA concentration variation amongst the treatments. The Duncan Multiple Range Test (DMRT) was used for multiple comparisons among the means of treatment at tα=5%, Results showed IBA concentrations significantly affected the rotting ability, the primary and secondary root length of shoot cutting (P < 0.05). On the other hand, the number of primary and secondary roots was not significantly different among treatment (P > 0.05). For rooting ability, 100 ppm of IBA concentration was the highest of all treatments. Meanwhile, 75 ppm of IBA concentration was the best treatment for development of root, i.e. the number of primary roots, the length primary and secondary roots.